Custom Made Acrylic Resin Ocular Prosthesis Using a Modified Technique: A Preliminary Report - Malaviya, Neha; Khanal, B; Yadav, A; Subhas, S (Journal of Universal College of Medical Sciences, 2015)
The loss of one eye may be due to a congenital defect, pathology or trauma requiring the surgical removal of eyeball. This causes significant physical and emotional disturbance to the patient. Psychological distress can be reduced by timely replacement with an artificial eye. This preliminary report describes the fabrication of the custom made acrylic resin ocular prosthesis (CMAROP) with a modified technique where a stock eye shell has been used to fabricate a custom ocular impression tray. Try in was done on the same day. The CMAROP achieves intimate contact with the tissue bed and creates functional and esthetically pleasing results. DOI: http://dx.doi.org/10.3126/jucms.v2i4.12068 Journal of Universal College of Medical Sciences (2014) Vol.02 No.04 Issue 08 Page: 41-44